Independence of an Advocate in Disciplinary Proceedings: Comparative Approach with a Focus on Ukrainian Experience - NAZAROV, Ivan V.; OVCHARENKO, Olena M.; KOVALYOVA, Yana O.; REMESKOVA, Yulia O. (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019, 2020)
This research brings a special focus on the notion of disciplinary liability of advocates, regarding their status in a legal system dedicated to universal standards of competitive fair trial. The article is based on experience of Ukraine in shaping an efficient system of the bar, with a wide comparative insight into the systems of disciplinary liability of lawyers in European counties. Universal standards of professional legal ethics are being peculiarly adverted. Safeguards of procedural independence of lawyers in disciplinary proceedings are presented regarding best European practices. It has been concluded that confidentiality is a cornerstone of professional status of a lawyer and limitations of this principal should be strictly envisaged by law. Otherwise, trustful relationships of a lawyer and his client would be challenged. Independence, due proceedings of investigation of disciplinary offences, proportionality are mentioned as basic principles on which the system of disciplinary liability of lawyers in a democratic society is being founded. Local bar associations play a leading role in protection of advocates’ professional rights and shielding them from unwanted attacks of any type, including infringements of procedural rights of lawyers, coming from law-enforcement authorities.